Feasibility Analysis of International Sea–Air Transport on the Export Cargo from East Asia to North America - ISHIHARA, Hiroyuki; ISHIGURO, Kazuhiko; TAKEBAYASHI, Mikio (Journal of the Eastern Asia Society for Transportation Studies, 2024)
The realization of international sea and air intermodal transportation (SEA&AIR transportation) will improve the competitiveness of international transportation by responding to recent advanced logistics needs, such as shorter transportation days, cost reduction, and environmental load reduction. This study analyzes the feasibility of SEA&AIR transportation via Japan using a generalized cost model. We found that (1) the possibility of SEA&AIR transportation from Kaohsiung to New York via Japan is the highest, with a share of 3.51%; (2) the larger share of marine transportation and the farther destination is a critical issue in realizing SEA&AIR transportation; and (3) SEA&AIR transportation takes over the share of air transportation. SEA&AIR transportation captures the share of air transportation and presents solutions that reduce environmental impact and energy efficiency by reducing air transportation.